Influence of Weed Control Methods on Yield and Quality of Cowpea Fodder - Yadav, Taramani; Chopra, Nisha K.; Chopra, N. K.; Kumar, Rakesh; Singh, Magan; Datt, Chander; Soni, P. G.; Rathore, Deepak Kumar; Kumar, Sourabh (Indian Journal of Animal Nutrition, 2018)
A field experiment was conducted during kharif season to study effect of different weed control methods on yield and quality of cowpea (Vigna unguiculata L. Walp) fodder. The experiment was performed using randomized block design with 10 treatment combinations viz. pendimethalin @ 1.0 kg a.i. (active ingredient)/ha PE (pre-emergence) + 1HW (hand weeding) at 40 DAS (H1), pendimethalin @ 1.0 kg a.i./ha PE(H2), oxyfluorfen @ 0.2 kg a.i./ha PE + 1HW at 40 DAS (H3), oxyfluorfen @ 0.2 kg a.i./ha PE (H4), imazethapyr @ 0.075 kg a.i./ha POE (post-emergence) at 20 DAS + 1HW at 40 DAS (H5), imazethapyr @ 0.075 kg a.i./ha POE at 20 DAS (H6), quizalofop-p-ethyl @ 0.025 kg a.i./ha POE at 20 DAS + 1HW at 40 DAS (H7), quizalofop-p-ethyl @ 0.025 kg a.i./ha POE at 20 DAS (H8), weed free (H9) and weedy check (H10) with four replications. Among weed control treatments, the green fodder yield was 68.35% higher with weed free than weedy check. Application ofpendimethalin @ 1.0 kg a.i./ha pre emergence along with one hand weeding at 40 days after sowing gave 53.06% and 45.01% higher green fodder yield over weedy check and quizalofop-p-ethyl applied @ 0.025 kg a.i./ ha post emergence at 20 days after sowing, respectively and lower NDF, ADF, hemicellulose at maturity with same treatment. Among various weed management options, application of pendimethalin @ 1.0 kg a.i./ha pre emergence along with one hand weeding at 40 days after sowing improved the yield and quality of cowpea fodder by controlling weeds throughout the crop season.